Stages d'enseignement dans les commissions scolaires anglophones du Québec - Pattison-Meek, Joanne; Henderson-Croteau, Ashley (Quebec English-speaking Communities Research Network (QUESCREN), 2025)
Chaque année, le gouvernement provincial finance des expériences de formation supervisées en milieu scolaire pour les stagiaires en enseignement, appelées « stages d’enseignement ». Le présent résumé examine la répartition de ces fonds entre les neuf commissions scolaires anglophones en fonction de la proportion de stagiaires en enseignement qu’elles accueillent en provenance des universités québécoises. Les données mettent en évidence une concentration des stages d’enseignement dans les commissions scolaires situées à proximité des universités anglophones et dans le grand Montréal, ce qui désavantage certaines écoles en régions rurales et éloignées.

Student Teacher Practicums in English School Boards in Quebec - Pattison-Meek, Joanne; Henderson-Croteau, Ashley (Quebec English-speaking Communities Research Network (QUESCREN), 2025)
Each academic year the provincial government provides financial support for supervised, in-school training experiences for student teachers, known as teaching practicums. This brief examines how these funds are distributed across the nine English school boards based on the proportion of student teachers they host from Quebec universities. The data highlights a concentration of teaching practicums undertaken in school boards with proximity to English universities and Greater Montreal, thereby disadvantaging some rural and remote schools.

EPCA Quebec Applauds Quebec Government's $300-Million Academic Catch-Up Plan: A Boost for Student Success - English Parents' Committee Association (EPCA) (2024)

Déclaration commune en réponse à un rapport publié par Mario Beaulieu, député / Joint Statement in Response to Report Released by Mario Beaulieu, M.P. - English Language Arts Network (ELAN); Quebec Writers' Federation (QWF); Quebec Drama Federation (QDF); Association of English-language Publishers of Quebec (AELAQ) (2023)
Keywords: Official Language Minority Community (OLMC)

Grâce à un financement de 1,1 million de dollars, 10 projets novateurs du FIC 2.0 prêtent assistance à 1 500 jeunes et aînés du Québec d’expression anglaise - Quebec Community Groups Network (QCGN) (2023)

Powered with $1.1 Million of Funding, 10 Innovative CIF 2.0 Projects Benefit 1,500 Youth and Seniors Across English-speaking Quebec - Quebec Community Groups Network (QCGN) (2023)

Renforcer la vitalité des communautés d'expression anglaise du Québec : Cadre normatif 2022-2025 - Québec. Secrétariat aux relations avec les Québécois d’expression anglaise (SRQEA) (2023)

Consensus on Language Issues in Quebec - Quebec Community Groups Network (QCGN); Association for Canadian Studies (2022)

Legault Government Must Backtrack on Dawson Decision: QCGN - Quebec Community Groups Network (QCGN) (2022)

QCGN : le gouvernement Legault doit faire marche arrière concernant sa décision au sujet de Dawson - Quebec Community Groups Network (QCGN) (2022)

ArtistsInspire Grants COVID-19 Protocol - English Language Arts Network (ELAN); Leading English Education and Resource Network (LEARN) (2022)

Community Development Plan for the English-speaking Community of Quebec 2022-2027 - Current Situation Report : Funding Roundtable - Quebec Community Groups Network (QCGN) (2021)
The Community Development Plan is a framework for collective action undertaken by the community sector of English-speaking Quebec to ensure its continued vitality. Through coordinated, strategic action, the community asserts collective control over resources allocated to it to ensure its development. The purpose of this report is to offer a portrait of the current situation of English-speaking Quebec’s Community sector with respect to the data development area. Together with similar reports in the other three areas, this provides a framework to help the Community Development Plan produce outcomes in line with our shared priorities.
Keywords: Official Language Minority Community (OLMC)

Projet 294 : Perspectives from Parents on the Overhaul of the Funding and Organization of Services for Handicapped Students and Students With Social Maladjustments or Learning Difficulties - English Parents' Committee Association (EPCA) (2021)

EPCA Lauds New Monies, Lifitng of Bureaucratic Controls : Disappointed in Lack of Option for Parents - English Parents' Committee Association (EPCA) (2020)

[Update to Parents Regarding Government Initiatives for 2020 School Year] - English Parents' Committee Association (EPCA) (2020)

10 Innovative Projects to Assist Vulnerable English-speaking Youth and Seniors - Quebec Community Groups Network (QCGN) (2020)

$1.1 Million Fund to Address Needs of Vulnerable English-speaking Youth and Seniors - Quebec Community Groups Network (QCGN) (2019)

Annual Funding from 2019-2023 : Artists Inspire Grants - English Language Arts Network (ELAN) (2019)
Support for Schools and Artists from Quebec's English-speaking communities to connect through hands-on creative experiences an ELAN/LEARN partnership funded by the Government of Canada's Action Plan for Official Languages

ELAN Quebec Thrilled with Government of Canada’s $7.5 Million Investment in Arts and Culture Micro-grants for Official Language Minority Schools - English Language Arts Network (ELAN) (2018)
Keywords: Official Language Minority Community (OLMC)

QCGN/Community Pleased with Funding from Secretariat - Quebec Community Groups Network (QCGN) (2018)

QCGN Welcomes New Federal Investments in English-speaking Quebec - Quebec Community Groups Network (QCGN) (2018)
Keywords: Official Language Minority Community (OLMC)

QCGN Welcomes New Budget Measures for English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2018)

QCGN Welcomes Promises of New Investments in Official Languages - Quebec Community Groups Network (QCGN) (2018)

Annex - List of Funded Projects - Quebec Community Groups Network (QCGN) (2017)

Social Initiatives to Address Needs of Vulnerable English-speaking Youth, Seniors and Newcomers - Quebec Community Groups Network (QCGN) (2017)

QCGN Hopeful About Opportunities for Official Language Minority Communities in Federal Budget - Quebec Community Groups Network (QCGN) (2017)
Keywords: Official Language Minority Community (OLMC)

QCGN Welcomes Resurrection of Independent Court Challenges Program - Quebec Community Groups Network (QCGN) (2017)

ELAN's ACE Initiative TEST! Projects Applicant Guide - Armeni, Virginia; Huff, Christie; Knowles, Paula; English Language Arts Network (ELAN) (2016)

English-speaking Quebecers to Benefit from Investment Fund for Official Language Minority Communities - Quebec Community Groups Network (QCGN) (2016)
Keywords: Official Language Minority Community (OLMC)

Bien vieillir dans sa langue, sa culture et sa communauté : soutien d'institutions fédérales clés et portrait des aînés anglophones du Québec - Canada. Office of the Commissioner of Official Languages (2013)
Cette étude exploratoire a deux grands objectifs. Le premier consiste à décrire le soutien qu’accorde le gouvernement fédéral au moyen de politiques et de programmes s’adressant aux aînés en général et aux aînés anglophones et francophones issus des communautés de langue officielle en situation minoritaire (CLOSM). Le deuxième objectif vise à brosser un portrait de la situation des aînés anglophones du Québec à l’aide de données. Pour ce faire, l’étude pose les questions suivantes : Où vivent les aînés anglophones du Québec? Qui sont-ils? Qui s’occupe d’eux? À quels services ont-ils accès, et comment utilisent-ils ces services? Nous espérons que l’étude aidera les CLOSM (y compris le nouvel organisme Aînés Action Québec, le réseau de défense des aînés anglophones de la province), à chercher du soutien des institutions fédérales.
Keywords: Official Language Minority Community (OLMC)

In the Know : Identifying Multiple Aspects of Quebec's Community Sector - Centre des organismes communautaires / Centre for community organizations (2012)
In October of 2008, The Centre for Community Organizations (COCo) began a community research project to help develop a better understanding of the diversity of groups working for social change in Québec. The study, “In the Know: Identifying multiple aspects of Québec’s community sector”, was supported by the Secretariat à l’Action Communautaire Autonome et aux Initiatives Sociales (SACAIS) and aimed to survey English-speaking, bilingual and ethno-cultural community groups across Québec over a three year period. The research was carried out between 2009 and 2012.

Alliance Quebec Shocked at PQ Government's Decision to Deny Quebecers Their Share of Federal Funding - Alliance Quebec (AQ) (2001)

Alliance Quebec Shocked at Landry's Refusal - Alliance Quebec (AQ) (2000)